1992
DOI: 10.1007/bf00300264
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic potential of human renal cell carcinoma: experimental model using subrenal capsule implantation in athymic nude mice

Abstract: Summary. The aim of this study was to determine whether subrenal capsule (SRC) implantation is a suitable model for the study of the metastatic potential of our human renal cell carcinoma (HRCC) lines and to establish new sublines with enhanced metastatic ability. NMRI athymic nude mice 7-11 weeks old received SRC implantation of our HRCC lines RC43 and RC21. These lines were not metastatic when implanted s.c. Mice were killed after 4 or 8 weeks, or when moribund. With the RC43 cell line the success rate for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…We showed that renal implantation of the KCI-18 cell line in the kidney of nude mice caused the formation of a primary kidney tumor that metastasizes to the lungs, liver and mesentery; mimicking the development and progression of metastatic RCC in human [2,3,21]. Our studies and others demonstrate that orthotopic models of heterotransplanted human RCC cells are representative of human RCC progression and preserve the karyotypic and histological characteristics of the human primary tumor [6-9,20]. These models can be used to study human RCC progression and metastasis and responsiveness of human RCC tumors to treatment in vivo .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We showed that renal implantation of the KCI-18 cell line in the kidney of nude mice caused the formation of a primary kidney tumor that metastasizes to the lungs, liver and mesentery; mimicking the development and progression of metastatic RCC in human [2,3,21]. Our studies and others demonstrate that orthotopic models of heterotransplanted human RCC cells are representative of human RCC progression and preserve the karyotypic and histological characteristics of the human primary tumor [6-9,20]. These models can be used to study human RCC progression and metastasis and responsiveness of human RCC tumors to treatment in vivo .…”
Section: Discussionmentioning
confidence: 84%
“…Among others, tumor xenograft models established in immunodeficient mice by implantation of RCC cells, isolated from a human tumor specimen, have been valuable to assess responsiveness to therapy [6-9]. To investigate the combination of radiotherapy with other treatment modalities, we have established a xenograft metastatic RCC tumor model by orthotopic renal implantation of a new KCI-18 human RCC cell line in athymic nude mice.…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture and conditions Two non-chemoselected human RCC cell lines, RC2 and RC21, originally established in our laboratory (Grossi et al 1992) and three resistant sublines were examined. All RCC cell lines were cultured in DMEM-F12 medium supplemented with 7.5% fetal calf serum, 1 E/ml penicillin, 1lg/ml streptomycin and 2 mM glutamine (Gibco BRL Europe, Breda, The Netherlands) at 37°C in a humidi®ed atmosphere supplemented with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…28 Orthotopic sites that most closely resemble the microenvironments in which human tumors develop are the most likely sites for successful tumor implantation. 28 In fact, it has been observed that orthotopically implanted human tumor xenografts have an increased chance of establishment, growth, and metastasis in immunodeficient animals when compared with nonorthotopically implanted xenografts, 28 as is the case with human renal cell carcinoma 29 and breast carcinoma. 30 Additionally, in experiments using the subcutaneous implantation method, only the cell strain MFH-3 consistently developed tumor nodules at the injection site.…”
Section: Discussionmentioning
confidence: 99%